Orthostatic Hypotension Predicts Cognitive Impairment in the Elderly: Findings from a Cohort Study - Huang, Haixia; Zheng, Tianheng; Liu, Fang; Wu, Zhuoli; Liang, Huazheng; Wang, Shaoshi (Frontiers in Neurology, 2017)
Background: Orthostatic hypotension (OH) is a known risk factor for cerebral ischemia, but its correlation with cognitive impairment (CI) is not well established. Objective: To explore the relationship between OH and CI in the elderly. Methods: The study group consisted of Forty-four OH patients who presented with drowsiness, vertigo and fatigue between Jan 2009 to Dec 2011 (OH group). Eighty-eight healthy elderly were paired with those in the OH group in 1:2 based on their education levels (NOH group). Baseline socio-demographic information and cognition-related measures were collected for both groups. Cognitive function was assessed 4 years later using MMSE. Results: The overall incidence of CI was 14.0% among the 114 subjects who completed the follow-up assessment. There was a significant difference in the incidence of CI between the OH group (23.7%) and the NOH group (9.2%) (χ2=4.399，P=0.036). After excluding the influence of age (OR=1.199, 95% CI: 1.072~1.340, P=0.001) and education years (OR=0.568, 95%CI: 0.371~0.869, P=0.009), OH (OR=4.047, 95% CI: 1.144~14.313, P=0.030) became an independent risk factor for cognitive impairment. Conclusions: OH can lead to cognitive impairment. We suggest that future studies, with a larger sample size, use OH exposure time instead of OH exposure population to verify the conclusion of the present study.